Modification of Carbon Nanotube for Synthesis of Titania Nanotube (Tint)-Carbon Nanotube (Cnt) Composite - Heltina, Desi (Journal of Energy, Mechanical, Material and Manufacturing Engineering, 2016)
Carbon nanotube (CNT) is a material widely chosen for object of research in nano technology. Apart from its good absorbent property, CNT also has a unique structure, superior mechanic and electric properties and its high strength. The property of CNT above is to be expected to improve performance of Titania nanotube (TiNT) composite. Properties of pure CNT are hydrophobic at the surface and low dispersion stability. To improve dispersability of CNT then modification need to be modified. Adding Cetyl trimethyl ammonium bromide (CTAB) surfactant on CNT is a way to increase dispersion stability of TiNT-CNT. The objective of the research was to study influence of adding of Cetyl trimethyl ammonium bromide (CTAB) surfactant to synthesis of TiNT-CNT composite in degrading phenol compound. Pure CNT was added with CTAB surfactant in liquid, then was sonificated and dried. Surfactant Cetyl trimethyl ammonium bromide (CTAB) added CNT then composited with TiNT. Phenol degradation then tested by using TiNT-CNT (CTAB) in reactor for 4.5 hours. Then sample was characterized by employing Field Emission Scanning Electron Microscopy (FESEM), X-ray Diffraction (XRD), Fourier Transform Infra-Red (FTIR) and UV-vis Spectroscopy. The result of experiments from FESEM characterization showed forming of TiNT-CNT composites morphology. From Xâray Diffraction (XRD) characterization showed crystal formed on TiNT-CNT only of anatase crystal. Degradation of TiNT-NT composite (CTAB) to phenol was also studied.